A spray process for improving the adhesion of a sprayed coating

CN122517253BActive Publication Date: 2026-10-16QINGQIJI ZHONGNENG (SUZHOU JIANGSU) HYDROGEN ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611018120.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-16
Estimated Expiration
2046-07-09

AI Technical Summary

Technical Problem

[0004]为此,本发明所要解决的技术问题在于克服现有技术中因基底表面凹坑内浆料填充不实、气泡残留及凸峰表面多余浆料干扰锚固结构形成而导致的涂层附着力不足问题,本发明提供了一种提升喷涂涂层附着力的喷涂工艺,在基底表面构筑具有特定深径比的凹凸结构,通过两次喷涂与中间清扫、静置沉降的工艺组合,在凹坑内部形成无气泡、紧实填充的独立锚固体,再通过二次喷涂实现锚固体与覆盖层的一体化融合,从而构建出具有高机械结合强度的涂层-基底界面

Benefits of technology

本发明所述的提升喷涂涂层附着力的喷涂工艺,通过分步喷涂和精细化处理,解决了现有水电解电极涂层附着力不足的问题。通过控制凹坑内浆料填充高度并形成预留空间,结合清扫处理和自然沉降,确保了锚固体内部的致密性并排除了气泡。后续覆盖层浆料与锚固体顶部的融合,形成了连续一体的涂层结构,提升了涂层与基底的结合强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122517253B_ABST
    Figure CN122517253B_ABST
Patent Text Reader

Abstract

The application discloses a spraying process for improving adhesion of a sprayed coating, comprising: surface treatment of a substrate to form a concave-convex structure with concaves and convexes; spraying of slurry to the substrate surface, control of the spraying amount to make the slurry filling height in the concaves 1 / 3-2 / 3 of the concave depth, and formation of a reserved space on the top of the concaves; cleaning before the slurry is dried to remove the slurry on the surface of the convexes, so that the top of the slurry in the concaves is not higher than the top surface of the convexes; horizontal static placement to make the slurry naturally settle and discharge air bubbles, and formation of a compact anchoring body; again spraying of the slurry to form a covering layer, the slurry of the covering layer entering the reserved space and being integrated with the top of the anchoring body into a continuous integrated structure; and solidification to form a coating. The process combination of twice spraying and intermediate cleaning and static settlement forms a bubble-free compact anchoring body in the concaves, and then is integrated with the covering layer, so that the bonding strength of the coating and the substrate is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coating preparation technology, and in particular to a spraying process for improving the adhesion of sprayed coatings. Background Technology

[0002] In water electrolysis for hydrogen production, the electrode, as the core component of the electrochemical reaction, has its lifespan and electrolysis efficiency directly determined by the adhesion of its surface coating. Industrial water electrolysis electrodes typically use nickel-based or stainless steel substrates. Coatings with high specific surface area and excellent catalytic activity are prepared on their surfaces through methods such as thermal spraying, plasma spraying, or brushing to reduce hydrogen or oxygen evolution overpotentials and improve the overall energy efficiency of the electrolyzer. As water electrolysis technology develops towards high current density and long-term continuous operation, the electrode coating is subjected to long-term heat stress from bubble erosion, electrolyte circulation, and frequent start-stop cycles. The bonding strength between the coating and the substrate becomes a key bottleneck restricting electrode durability. Insufficient coating adhesion can easily lead to localized peeling, flaking, or even large-area detachment. This not only causes a sharp decline in catalytic activity, increased cell pressure, and increased energy consumption, but the detached coating fragments can also block electrolyte circulation channels or damage the diaphragm, causing serious safety hazards and equipment failures.

[0003] To address the aforementioned issue of insufficient coating adhesion, existing technologies generally employ two improvement strategies. The first is surface roughening of the substrate, using methods such as sandblasting, acid etching, or electrical discharge machining to increase surface roughness and improve the bonding strength between the coating and the substrate through mechanical interlocking. The second is adding a transition layer or intermediate layer between the substrate and the functional coating, utilizing the good compatibility between the intermediate layer material and the substrate and coating to alleviate interfacial stress and reduce the tendency for interfacial cracking due to differences in thermal expansion coefficients. While these two approaches can improve the initial adhesion of the coating to some extent, significant defects still emerge during actual long-term service. Although sandblasting or acid etching can create a rough surface, during the direct application of the slurry, it is difficult for the slurry to fully penetrate the bottom of the pit and completely expel air, resulting in residual microbubbles or pores inside the anchoring point. These interfacial defects become stress concentration sources and crack initiation sources during subsequent service, gradually expanding under the influence of bubble erosion and thermal cycling, ultimately causing the coating to detach from the root of the anchoring point, with the coating adhesion falling far short of theoretical expectations. The transition layer solution can only improve the chemical compatibility of the interface, but it cannot solve the physical defects inside the mechanical anchoring structure, and it increases the complexity of the process and the manufacturing cost. Summary of the Invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the problem of insufficient coating adhesion caused by incomplete filling of slurry in the pits of the substrate surface, residual air bubbles, and interference of excess slurry on the surface of the convex peaks with the formation of the anchoring structure in the prior art. The present invention provides a spraying process to improve the adhesion of the sprayed coating. A concave-convex structure with a specific depth-to-diameter ratio is constructed on the substrate surface. Through a combination of two spraying processes and intermediate cleaning and static settling, an independent anchor body with no air bubbles and tight filling is formed in the pit. Then, the anchor body and the cover layer are integrated and fused through a second spraying, thereby constructing a coating-substrate interface with high mechanical bonding strength.

[0005] To address the aforementioned technical problems, this invention provides a spraying process for improving the adhesion of sprayed coatings, comprising the following steps: The substrate surface is treated to form an uneven structure with pits and peaks; The slurry is sprayed onto the substrate surface using a spraying device, so that the slurry covers both the convex surface and the inside of the pits of the substrate at the same time. The amount of spraying is controlled so that the filling height of the slurry in the pit is 1 / 3 to 2 / 3 of the pit depth, and a reserved space is formed at the top of the pit. Before the slurry dries, clean along the substrate surface to remove the slurry covering the surface of the peaks, while ensuring that the top of the slurry remaining in the pits does not exceed the top surface of the peaks. The base is placed horizontally, allowing the slurry in the pit to settle naturally under gravity, expelling air bubbles and forming a compact anchor body. The slurry is sprayed onto the substrate surface again using a spraying device to form a covering layer on the surface of the anchor body and the protruding surface of the substrate. The slurry of the covering layer enters the reserved space in the pit and merges with the top of the anchor body to form a continuous integrated structure. The coating is cured to form a coating that adheres to the surface of the substrate.

[0006] In one embodiment of the present invention, the method for treating the substrate surface to form an uneven structure with pits and peaks is as follows: the substrate surface is treated by physical impact method, chemical dissolution method or thermal ablation method to form randomly distributed or regularly arranged pits and peaks on the substrate surface, and the opening width of the pits is controlled to be 50 to 500 μm, the pit depth is 30 to 100 μm, and the surface roughness is 30 to 80 μm.

[0007] In one embodiment of the present invention, the cleaning process along the substrate surface includes: scraping with a scraper and purging with airflow, wherein: when the substrate is a dense and rigid substrate such as a nickel plate, the cleaning process is scraping with a scraper; when the substrate is a porous and flexible substrate such as nickel foam or metal fiber felt, the cleaning process is purging with airflow.

[0008] In one embodiment of the present invention, the scraping process includes: scraping along the substrate surface with a scraper, the gap between the scraper and the top surface of the peak is 0 to 30 μm, the slurry on the surface of the peak is scraped off by the scraper, and the slurry in the pit is not in contact with the scraper because it is lower than the top surface of the peak, and is thus retained inside the pit.

[0009] In one embodiment of the present invention, the airflow purging process includes: using compressed air to tangentially purge along the substrate surface at a speed of 10 to 30 m / s, using the shear force of the airflow to blow away the slurry covering the surface of the peak, while the slurry in the pit avoids the shearing effect of the airflow because it is lower than the top surface of the peak, and is thus retained inside the pit.

[0010] In one embodiment of the present invention, after the cleaning process is completed and before the substrate is horizontally placed, a pressure pulse is applied to the top of the slurry in the pit and towards the bottom of the pit. The pressure of the pressure pulse is set to 0.1 to 0.5 MPa, the pulse duration is 0.1 to 1.0 seconds, and the number of pulses is 1 to 5 times, so as to force the slurry in the pit to adhere tightly to the bottom and inner wall of the pit.

[0011] In one embodiment of the present invention, during the horizontal settling process, mechanical vibration with a frequency of 10 to 30 Hz and an amplitude of 0.1 to 0.5 mm is applied to accelerate the rise of residual air bubbles inside the slurry in the pit to the liquid surface for discharge.

[0012] In one embodiment of the present invention, when the slurry is sprayed onto the substrate surface for the first time using a spraying device, the spraying pressure of the spraying device is 1.5 to 4.0 MPa and the spraying angle is 30 to 60°. The slurry impacts the substrate surface at an oblique angle, causing the slurry to enter the pit under the push of the spraying pressure and accumulate at the bottom of the pit. At the same time, the oblique impact causes the slurry to spread along the inner wall of the pit.

[0013] In one embodiment of the present invention, when the slurry is sprayed onto the substrate surface again using a spraying device, the spraying pressure of the spraying device is 0.3 to 1.2 MPa and the spraying angle is 70 to 90°. The slurry settles vertically or nearly vertically onto the substrate surface in a fine atomized state, forming a uniformly thick covering layer, and will not damage the formed anchor body due to excessive impact force.

[0014] In one embodiment of the present invention, after the coating layer is sprayed and before the curing process, a secondary cleaning process is performed along the substrate surface to remove excess slurry at the peaks of the coating layer where the thickness is greater than that at the pits, so that the difference between the coating layer thickness at the top of the peaks and the coating layer thickness above the pits does not exceed 5 μm.

[0015] The technical solution of the present invention has the following advantages compared with the prior art: The spraying process described in this invention, which enhances the adhesion of sprayed coatings, solves the problem of insufficient adhesion in existing water electrolysis electrode coatings through step-by-step spraying and refined processing. By controlling the filling height of the slurry within the pits and creating reserved spaces, combined with cleaning and natural settling, the internal density of the anchor body is ensured and air bubbles are eliminated. The subsequent fusion of the cover layer slurry with the top of the anchor body forms a continuous and integrated coating structure, improving the bonding strength between the coating and the substrate. Attached Figure Description

[0016] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings, wherein: Figure 1 This is a flowchart of the spraying process for improving the adhesion of the sprayed coating according to the present invention; Figure 2 These are physical images of the adhesion test of the present invention; wherein: (a) is the physical image corresponding to Example 1; (b) is the physical image corresponding to Comparative Example 1; (c) is the physical image corresponding to Comparative Example 2; and (d) is the physical image corresponding to Comparative Example 3. Figure 3 This is an electron microscope image of Embodiment 1 of the present invention; Figure 4 This is an electron microscope image of Comparative Example 1 of the present invention; Figure 5 This is an electron microscope image of Comparative Example 2 of the present invention; Figure 6 This is an electron microscope image of Comparative Example 3 of the present invention. Detailed Implementation

[0017] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.

[0018] Reference Figure 1As shown, the spraying process for improving the adhesion of sprayed coatings according to the present invention first treats the substrate surface to form an uneven structure with pits and peaks. Specifically, physical impact methods, chemical dissolution methods, or thermal ablation methods can be used. Physical impact methods, such as sandblasting, shot peening, or laser impact, create microscopic depressions and roughness on the substrate surface through mechanical force, applicable to various materials, and effectively increase surface area and provide mechanical interlocking points. Chemical dissolution methods selectively dissolve the substrate surface using chemical etchants, such as acid etching or alkaline etching, to form textured structures. This method allows for precise control of etching depth and pattern. Thermal ablation methods, such as laser ablation or plasma ablation, utilize high-energy sources to remove material, forming fine pits and trenches, offering high precision and controllability. These methods provide diverse means to prepare the desired uneven structure, which can be flexibly selected according to the substrate material characteristics and process requirements.

[0019] The pits and peaks formed on the substrate surface can be randomly distributed or regularly arranged. Randomly distributed pits and peaks are typically formed by sandblasting or maskless chemical etching, providing an overall roughening effect and increasing surface area. Regularly arranged pits and peaks can be achieved through laser patterning, photolithography combined with etching, or precision machining, which helps optimize the mechanical interlocking effect and may better control stress distribution. To ensure that the slurry can effectively fill and form a stable anchor, this application precisely defines the geometric parameters of the pits. The opening width of the pits is controlled between 50 and 500 μm to ensure that the slurry can enter smoothly and form a sufficient anchor volume, while avoiding excessively large openings that may affect the substrate strength. The pit depth is controlled between 30 and 100 μm to provide sufficient embedding depth for the slurry to form a strong mechanical interlock. The surface roughness is controlled between 30 and 80 μm to ensure that the substrate surface has sufficient microtexture to enhance the physical adsorption and mechanical interlocking force between the slurry and the substrate, while avoiding excessive roughness that may lead to uneven coating or stress concentration.

[0020] Subsequently, the slurry is sprayed onto the substrate surface using a spraying device, simultaneously covering both the surface of the peak and the interior of the pit. In this step, the key control parameter is the spray volume, ensuring the slurry filling height within the pit is controlled between one-third and two-thirds of the pit's depth, leaving unoccupied space at the top of the pit. This reserved space serves a dual purpose: firstly, it provides leeway for removing slurry from the peak surface during subsequent cleaning, preventing scratching of the already filled slurry inside the pit; secondly, it provides fusion space for the subsequent overlay slurry to enter during the second spraying, allowing it to flow smoothly and bond with the top of the anchor.

[0021] When the slurry is sprayed onto the substrate surface for the first time using a spraying equipment, the spraying pressure of the spraying equipment is 1.5 to 4.0 MPa and the spraying angle is 30 to 60°. The slurry impacts the substrate surface at an angle, causing the slurry to enter the pit under the propulsion of the spraying pressure and accumulate at the bottom of the pit. At the same time, the angled impact causes the slurry to spread along the inner wall of the pit.

[0022] Specifically, spray pressure is a key parameter affecting the kinetic energy and penetration of the slurry. Higher spray pressure imparts sufficient kinetic energy to the slurry particles, giving them a stronger impact force upon impacting the substrate surface. This overcomes surface tension and air resistance, effectively propelling the slurry deep into the recesses and ensuring thorough filling of the bottom. The pressure range is designed to ensure effective slurry entry into the recesses while avoiding unnecessary damage to the substrate structure from excessive pressure. The spray angle refers to the angle between the nozzle axis and the normal to the substrate surface. When the spray angle is set between 30° and 60°, the slurry impacts the substrate surface at an oblique angle. This oblique impact differs from a vertical impact; it provides downward pressure while also contributing a shear force component along the substrate surface, aiding in the lateral spread of the slurry within the recesses. An oblique impact refers to the slurry flow striking the substrate at an angle not perpendicular to the substrate surface. This impact method generates a force component along the substrate surface, allowing the grout to not only fill downwards after entering the pit but also spread outwards along the inner wall of the pit, thereby increasing the coverage of the pit's inner wall and the contact area between the grout and the inner wall. The injection pressure is the driving force that enables the grout to overcome air resistance, surface tension, and its own viscosity inside the pit, achieving effective filling. Under sufficient pressure, the grout can be forcibly pressed deep into the pit, forming an initial aggregate layer at the bottom, laying the foundation for subsequent spreading and anchoring. The shear force component generated by the oblique impact guides the grout, after aggregating at the bottom of the pit, to spread upwards or outwards along the sidewalls of the pit. This spreading action helps the grout uniformly cover the entire inner surface of the pit, eliminating any possible voids or unwetted areas, thus forming a more complete and denser anchor.

[0023] Before the slurry dries, a cleaning process is performed along the substrate surface to remove the slurry covering the surface of the peak. In the prior art, the slurry covering the surface of the peak, after curing, becomes bonded to the anchor body in the pit, forming a continuous covering layer. However, because the slurry on the peak surface is weakly constrained by the substrate during curing and shrinkage, it is prone to microcracks. These microcracks propagate continuously along the slurry towards the interior of the pit, damaging the structural integrity of the anchor body. This invention removes the slurry from the peak surface before it dries through a cleaning step, completely separating the slurry in the pit from the slurry on the peak surface, creating an independent slurry body. Simultaneously, the cleaning process ensures that the top of the slurry remaining in the pit does not exceed the top surface of the peak, ensuring that the settlement of the slurry during subsequent settling is not affected by the pull of the residual slurry on the peak surface.

[0024] In the embodiments of this application, a cleaning method along the substrate surface is proposed, including scraping with a scraper and air purging. When the substrate is a dense and rigid substrate such as a nickel plate, the cleaning is performed by scraping with a scraper; when the substrate is a porous and flexible substrate such as nickel foam or metal fiber felt, the cleaning is performed by air purging.

[0025] The cleaning process aims to precisely control the distribution of the slurry on the substrate surface, removing excess slurry from the surface of peaks while ensuring that slurry is retained inside the depressions, with its top not exceeding the peak's surface. Its purpose is to create conditions for subsequent anchor formation and to prevent the slurry on the peak surface from adversely affecting the adhesion of the subsequent capping layer. The implementation method of the cleaning process needs to be selected and optimized based on the physical characteristics of the substrate.

[0026] The scraping process involves using a scraper to scrape along the substrate surface, with a gap of 0–30 μm between the scraper and the top surface of the protrusion. The slurry on the protrusion surface is scraped off by the scraper, while the slurry in the depressions, being below the top surface of the protrusion, does not contact the scraper and is thus retained inside the depressions. Specifically, scraping along the substrate surface with a scraper refers to using a mechanical scraper to move linearly or curvilinearly across the substrate surface, removing the slurry adhering to the protrusion surface through physical contact. This linear scraping method provides stable scraping force, ensuring uniform removal of slurry from the protrusion surface. The scraper is typically made of wear-resistant materials that do not chemically react with the slurry, such as polyurethane, stainless steel, or ceramic, to ensure scraping effectiveness and scraper lifespan. The gap between the scraper and the top surface of the protrusion is precisely controlled within the range of 0–30 μm. When the gap is 0 μm, the scraper directly contacts the top surface of the protrusion, maximizing the removal of slurry from the protrusion surface and even allowing for slight cleaning or smoothing of the protrusion surface. When the gap is 30μm, a tiny void exists between the scraper and the top surface of the peak. In this case, the scraper mainly removes the slurry through shearing or squeezing action, while reducing wear on the peak itself. By adjusting this gap, effective removal of slurry from the peak surface can be achieved, and substrate protection can be optimized, depending on the specific conditions such as the viscosity and thickness of the slurry and the hardness of the substrate material.

[0027] Airflow purging involves using compressed air to tangentially purge the substrate surface at a velocity of 10–30 m / s. The shear force of the airflow removes the slurry covering the peaks, while the slurry in the depressions, being below the peak tops, avoids this shear force and remains inside. Specifically, airflow purging is a method that uses high-speed airflow to physically act on the substrate surface to selectively remove slurry from specific areas. Its core lies in controlling the airflow parameters and action mode to achieve precise slurry removal while protecting slurry that should not be removed. Using compressed air as the purging medium provides a stable and controllable airflow. Tangential purging means the airflow direction is roughly parallel to the substrate surface, rather than perpendicular. This tangential action generates effective shear force, facilitating the peeling and removal of slurry adhering to the peaks while reducing direct impact on the slurry inside the depressions, thus lowering the risk of it being blown out. Airflow velocity is a key parameter affecting the purging effect. The airflow velocity is controlled within the range of 10–30 m / s to provide sufficient kinetic energy and shear force to effectively overcome the adhesion between the slurry and the peak surface, causing it to detach. If the velocity is too low, the slurry may not be effectively removed; if the velocity is too high, it may cause excessive disturbance to the slurry in the pit, or even blow it out. Velocities within this range enable efficient and precise slurry removal. During tangential purging, the airflow generates relative motion with the substrate surface and the slurry layer, thus creating shear force. This shear force acts on the slurry covering the peak surface. When the shear force exceeds the adhesion between the slurry and the substrate peak surface, the slurry is peeled off and carried away by the airflow. This is the core physical mechanism for selectively removing slurry. Since the slurry filling height in the pit is controlled to be 1 / 3 to 2 / 3 of the pit depth, and its top is not higher than the peak top surface, the airflow mainly acts on the peak surface during tangential purging. Because the slurry inside the pit is positioned below the main area of ​​airflow, it can effectively avoid the direct shearing and impact of the airflow, thus ensuring that it is retained inside the pit and preventing it from being accidentally removed.

[0028] After cleaning, the substrate is placed horizontally. During this settling process, the slurry within the pit settles naturally under gravity. Solid particles in the slurry deposit towards the bottom of the pit, while the less dense liquid components migrate upwards. Air bubbles entrained during spraying rise to the surface and burst under buoyancy. This physical settling process gradually densifies the slurry within the pit, forming a compact anchor. Because the top of the slurry is lower than the top of the peak, the free surface of the slurry remains within the pit during the settling process, undisturbed by external forces. This allows sufficient time for air bubbles to escape, thus completely eliminating the porosity and looseness defects within the anchoring points found in traditional processes.

[0029] In this embodiment, under gravity alone, residual air bubbles may remain inside the slurry, which are difficult to completely expel. These bubbles can affect the density and strength of the anchoring solid, thereby reducing the adhesion of the coating. To address this, this application further proposes that during the horizontal settling process, mechanical vibration with a frequency of 10–30 Hz and an amplitude of 0.1–0.5 mm is applied to accelerate the rise of residual air bubbles inside the slurry within the pit to the surface for expulsion. The horizontal settling process refers to maintaining a horizontal state on the substrate after cleaning and before re-coating the slurry, allowing the slurry in the pit to undergo initial settling and air bubble expulsion under gravity. The introduced mechanical vibration aims to apply periodic disturbance to the slurry through external energy input. This mechanical vibration can be generated by a vibration table, ultrasonic vibrator, or eccentric motor, and the vibration energy is transferred to the slurry within the pit through contact or coupling with the substrate. The vibration frequency is set within the range of 10–30 Hz to provide sufficient energy to propel the bubbles while preventing excessive disturbance or splashing of the slurry. The amplitude is controlled within 0.1–0.5 mm to ensure moderate vibration intensity, effectively promoting bubble rise without damaging the initial structure of the slurry or causing it to overflow from the pits. Through this controlled mechanical vibration, residual bubbles inside the slurry gain additional kinetic energy, overcoming the viscous resistance of the slurry, accelerating their movement towards the liquid surface, and ultimately being discharged.

[0030] In other embodiments, this application also proposes, after cleaning and before horizontally placing the substrate, applying a pressure pulse toward the bottom of the pit to the top of the slurry in the pit, setting the pressure of the pressure pulse to 0.1 to 0.5 MPa, the pulse duration to 0.1 to 1.0 seconds, and the number of pulses to 1 to 5 times, so as to force the slurry in the pit to adhere tightly to the bottom and inner wall of the pit.

[0031] Specifically, this step aims to assist in the densification of the slurry and its adhesion to the pit walls through external mechanical force. After cleaning and before the substrate is horizontally settled, a momentary, directional downward pressure is applied to the top of the undried slurry within the pit using a pneumatic device or mechanical pressure head. This pressure pulse effectively compacts the slurry and promotes close contact between the slurry and the bottom and inner walls of the pit. The pressure of the pressure pulse is a key parameter for achieving effective compaction. If the pressure is too low, it may be insufficient to overcome the viscous resistance of the slurry, failing to effectively compact the slurry or expel air bubbles; if the pressure is too high, it may cause slurry splashing, damage to the pit structure, or even affect the integrity of the substrate. Therefore, controlling the pressure within the range of 0.1–0.5 MPa ensures that the slurry is subjected to appropriate pressure while avoiding negative effects, thereby achieving effective densification. The pulse duration determines the length of time the slurry is compressed. Too short a duration may result in the slurry not fully responding to pressure before it is released, leading to poor compaction; too long a duration may cause unnecessary energy consumption and premature drying of the slurry surface, affecting subsequent operations. Setting the pulse duration to 0.1–1.0 seconds provides sufficient response time for the slurry to flow, fill, and expel air bubbles during pressure application. The number of pulses refers to the number of repetitions of applying pressure pulses to the same area. A single pulse may not be sufficient to completely eliminate air bubbles in the slurry or achieve the desired compaction. Repeated pulse application can further promote slurry compaction and air bubble expulsion. However, too many pulses may lead to inefficiency and even cause unnecessary disturbance to the slurry or substrate. Therefore, controlling the number of pulses to 1–5 ensures both compaction effectiveness and process efficiency and stability.

[0032] After settling, the slurry is sprayed onto the substrate surface again using a spraying device. At this point, a dense and compact anchor body has formed inside the recess, with the top of the anchor body lower than the top of the peak. The second sprayed slurry not only covers the surface of the peak but also enters the reserved space at the top of the recess, wetting and fusing with the top of the anchor body at the interface. After curing, it forms a continuous, integrated structure from the bottom of the recess to the surface of the peak. Because the anchor body has already been densified, the second sprayed slurry only needs to fill the space at the top of the recess and will not cause impact damage to the internal structure of the already formed anchor body.

[0033] Specifically, when the slurry is sprayed onto the substrate surface again using a spraying device, the spraying pressure is controlled between 0.3 and 1.2 MPa. This relatively low spraying pressure ensures that the slurry forms a fine atomization upon leaving the nozzle, while preventing the slurry from impacting the substrate surface with excessive kinetic energy. If the spraying pressure is too high, the impact force of the slurry is too great, which may damage the formed anchor body; if the spraying pressure is too low, the atomization effect of the slurry is poor, which may lead to uneven coverage. The spraying angle is set to 70–90°, that is, the slurry is sprayed in a direction perpendicular or nearly perpendicular to the substrate surface. This spraying method allows the slurry to uniformly cover the substrate surface by settling rather than impacting, minimizing the lateral shear force or vertical impact force on the anchor body, which is conducive to the smooth filling of the reserved space and fusion with the anchor body. Under the synergistic effect of the above-mentioned spraying pressure and spraying angle, the slurry is atomized into extremely fine droplets and slowly settles onto the substrate surface in a near-vertical direction. A fine atomization helps the slurry spread evenly and avoids agglomeration, while vertical or near-vertical settling ensures that the slurry can smoothly enter the reserved space within the recess and fully contact and fuse with the top of the anchor body, while forming a uniform coverage on the surface of the peak. Through the precise control of these spraying parameters, a uniformly thick coating layer can be formed across the entire substrate surface. A uniform coating layer is crucial for subsequent curing, preventing stress concentration, cracking, or localized performance differences caused by uneven thickness, thus ensuring the overall performance of the coating. Furthermore, by reducing the spray pressure and using a vertical or near-vertical spraying angle, the impact kinetic energy of the slurry is significantly reduced, effectively protecting the well-adhesive anchor body structure formed after the first spraying step and preventing mechanical damage or structural loosening during the second spraying process.

[0034] Finally, a curing process is performed to cross-link and solidify the coating as a whole, forming a coating structure attached to the substrate surface. In this coating, the anchor body is equivalent to a rivet structure embedded inside the pit, which fuses with the cover layer at the top of the pit to form a whole. There is no mechanical interface or layer separation between the two, and the mechanical bonding strength is far superior to the structure formed by the simultaneous curing of the cover layer and the slurry inside the pit in the traditional process.

[0035] In some of the above embodiments, during the formation of the coating layer, due to the operating characteristics of the spraying equipment and the influence of the uneven structure of the substrate surface, the deposition thickness of the slurry on the surface of the substrate peaks and above the pits may differ. Generally, a thicker coating layer is more likely to form at the peaks, while the coating layer above the pits may be relatively thin. This uneven thickness will affect the overall smoothness and uniformity of the coating, and may introduce internal stress during the subsequent curing process, even affecting the long-term stability and adhesion of the coating.

[0036] In this regard, this application further proposes that after the coating layer is sprayed and before the curing process, a secondary cleaning process is performed along the substrate surface to remove excess slurry at the peaks of the coating layer where the thickness is greater than that at the pits, so that the difference between the coating layer thickness at the top of the peaks and the coating layer thickness above the pits does not exceed 5μm.

[0037] This secondary cleaning process aims to refine the already sprayed coating layer, eliminating any thickness unevenness that may have occurred during the spraying process. This can be achieved, but is not limited to: gently scraping with a flexible scraper or blade to remove excessively thick slurry at the peaks; or using low-pressure airflow for precise purging, selectively removing excess slurry from the peak surface by controlling the direction, speed, and duration of the airflow. Alternatively, suction rollers or brushes can be used to homogenize the surface slurry without damaging the overall structure of the coating. The core of this operation lies in precisely controlling the removal amount, ensuring that the coating thickness at the peaks is consistent with the coating thickness above the pits. By removing excess slurry at the peaks, coating defects caused by localized excessive thickness can be effectively avoided, such as uneven drying shrinkage and stress concentration during curing. Controlling the difference in coating thickness between the top of the peaks and the area above the pits to no more than 5 μm sets a high standard for coating thickness uniformity. Controlling the thickness difference to within 5μm means that the coating surface meets extremely high smoothness requirements. This not only helps improve the aesthetics of the coating, but more importantly, it ensures the consistency of the physical properties (such as hardness, abrasion resistance, conductivity, etc.) of the coating across the entire substrate surface, thereby significantly improving the overall performance and service life of the coating.

[0038] Through the above technical solution, the present invention can achieve the following beneficial effects: First, the slurry in the pit becomes completely dense after natural settling, and the air bubbles are fully discharged. There are no pores or loose defects inside the anchor body, which fundamentally eliminates the stress concentration and crack propagation problems caused by interface pores during the service of traditional coatings. This significantly improves the structural integrity of the anchor body, enabling it to withstand the erosion of air bubbles and thermal cycling impact for a long time without internal damage.

[0039] Secondly, the cleaning step removes the slurry on the surface of the protrusion before curing, so that the anchor body is in an independent state during the formation process. This avoids the stretching damage of the slurry in the pit caused by the curing shrinkage of the slurry on the surface of the protrusion. At the same time, it ensures that the reserved space between the top of the anchor body and the top surface of the protrusion is fully utilized, providing a reliable fusion interface for the secondary spray coating layer.

[0040] Third, the secondary spraying allows the coating slurry to fuse with the top of the anchor body in an uncured state, forming a continuous integrated structure after curing. This eliminates the weak interface bonding problem present in traditional transition layer or intermediate layer solutions. The coating and the substrate have both mechanical interlocking and anchoring as well as interface chemical bonding, resulting in a significant improvement in bonding strength.

[0041] Fourth, the cover layer is directly bonded to the surface of the substrate peak, and the top surface of the peak remains clean after cleaning. The secondary sprayed slurry can fully wet and contact it, avoiding the risk of microcracks formed by the curing and shrinkage of the slurry on the peak surface in traditional processes propagating into the coating. The cover layer itself has higher structural integrity and density.

[0042] This invention can be widely applied to the preparation of various functional coatings, including but not limited to electrochemical electrode catalytic layers, anti-corrosion coatings, and thermal barrier coatings. It is especially suitable for the large-area spraying preparation of water electrolysis hydrogen production electrode catalytic layers, which enhances the electrode's ability to resist bubble erosion, electrolyte impact and thermal stress alternation during long-term service, and extends the service life of the electrode.

[0043] To further illustrate that the spraying process of this application can significantly improve the adhesion of the coating compared with the prior art, this application also conducted experimental verification, setting up Example 1 using the technical solution of this application and Comparative Examples 1, 2, and 3 of the prior art.

[0044] Example 1: A spraying process for improving the adhesion of a sprayed coating, provided in this application, is described in the following steps: Substrate preparation: Nickel foam (1.5 mm thickness, 200 μm average pore size, 350 g / m² areal density) was selected as the substrate. Its inherent uneven structure eliminates the need for surface treatment. The nickel foam was cut into 50 mm × 50 mm pieces and ultrasonically cleaned sequentially in acetone, anhydrous ethanol, and deionized water for 10 minutes each. After cleaning, the pieces were dried in a 60°C oven for 2 hours before use.

[0045] Slurry preparation: NiFe-LDH catalyst powder was dispersed in deionized water, and PTFE emulsion was added as a binder (PTFE to catalyst powder mass ratio of 1:10). The mixture was stirred and stirred until homogeneous, and the solid content was adjusted to 45wt% to obtain a high solid content slurry. A portion of the slurry was diluted to a solid content of 20wt% and used as a slurry for the coating layer spraying.

[0046] Spraying Process: A high-pressure airless spray gun is used to spray a slurry with a solid content of 45 wt% onto the surface of the nickel foam. The spraying pressure is 2.5 MPa, and the spraying angle is 45°. The spraying amount is controlled so that the slurry filling height in the pit is half the pit depth. Within 30 seconds after spraying, an air knife is used to tangentially blow along the surface of the nickel foam at an airflow velocity of 20 m / s for 3 seconds to remove the slurry covering the surface of the peaks, while ensuring that the top of the slurry remaining in the pit is lower than the top surface of the peaks. The nickel foam is then left to stand horizontally for 5 minutes to allow the slurry in the pits to settle naturally under gravity, expelling air bubbles and forming a compact anchor. Subsequently, using the same spray gun, a slurry with a solid content of 20 wt% is sprayed onto the surface of the nickel foam at a spraying pressure of 0.6 MPa and a spraying angle of 85° to form a cover layer with a thickness of 50 μm. During the spraying process, the cover layer slurry enters the reserved space at the top of the pit, contacts and fuses with the top of the anchor. The coated specimens were placed in an oven and dried at 120°C for 20 minutes. Then, they were sintered in a muffle furnace at 350°C for 60 minutes and cooled to room temperature with the furnace to obtain coated nickel foam specimens.

[0047] Comparative Example 1 differs from Example 1 in that: after the first spraying, no cleaning is performed, i.e., no airflow is used to remove the slurry covering the peak surface; the rest of the operation is exactly the same as in Example 1.

[0048] Specifically, after cleaning and drying, a slurry with a solid content of 45 wt% was sprayed onto the surface of the nickel foam using a high-pressure airless spray gun. The spraying pressure was 2.5 MPa, the spraying angle was 45°, and the spraying amount was controlled so that the slurry filling height in the pits was half the pit depth. After spraying, the nickel foam was placed horizontally for 5 minutes. Then, a slurry with a solid content of 20 wt% was sprayed onto the substrate surface using the same spray gun to form a cover layer. The spraying pressure was 0.6 MPa, the spraying angle was 85°, and the cover layer thickness was controlled to be 50 μm. The drying and sintering conditions were the same as in Example 1.

[0049] Comparative Example 2 differs from Example 1 in that: during the first spraying, the amount of spraying is controlled to completely fill the pit with slurry (the filling height is equal to the pit depth), no space is reserved, and no second spraying (covering layer) is performed. The remaining operations are the same as in Example 1.

[0050] Specifically, after cleaning and drying, a slurry with a solid content of 45 wt% was sprayed onto the surface of the nickel foam using a high-pressure airless spray gun. The spraying pressure was 2.5 MPa, the spraying angle was 45°, and the spraying amount was controlled to completely fill the pits with slurry until it was flush with the top surface of the peaks. Within 30 seconds after spraying, an air knife was used to tangentially blow along the surface of the nickel foam at an airflow velocity of 20 m / s for 3 seconds to remove the slurry covering the peaks, ensuring that the top of the slurry in the pits was flush with the top surface of the peaks without any pre-reserved space. After the nickel foam was horizontally placed for 5 minutes, it was directly dried and sintered without a second spraying. The drying and sintering conditions were the same as in Example 1.

[0051] Comparative Example 3 differs from Example 1 in that: after the first spraying and cleaning, no horizontal resting is performed, and the second spraying (covering layer) is performed directly. The remaining operations are the same as in Example 1.

[0052] Specifically, after cleaning and drying, a slurry with a solid content of 45 wt% was sprayed onto the surface of the nickel foam using a high-pressure airless spray gun. The spraying pressure was 2.5 MPa, the spraying angle was 45°, and the spraying amount was controlled so that the slurry filling height in the pits was half the pit depth. Within 30 seconds after spraying, an air knife was used to tangentially blow along the surface of the nickel foam at an airflow velocity of 20 m / s for 3 seconds to remove the slurry covering the peaks. Immediately after cleaning, a slurry with a solid content of 20 wt% was sprayed onto the substrate surface using the same spray gun to form a coating layer. The spraying pressure was 0.6 MPa, the spraying angle was 85°, and the coating layer thickness was controlled to be 50 μm. The drying and sintering conditions were the same as in Example 1.

[0053] Adhesion tests were performed on the coating specimens obtained in Example 1 and Comparative Examples 1-3.

[0054] Cross-cut adhesion test: Performed according to national standard GB / T9286-2021 "Cross-cut test for paints and varnishes". Use a cross-cutting tool to cut 1mm × 1mm squares into the coating surface of each test piece, ensuring the cuts penetrate the coating to the substrate. Gently remove loose coating debris from the cut areas with a soft brush. Apply 25mm wide transparent pressure-sensitive adhesive tape to the cut areas, pressing firmly with your fingers to ensure tight adhesion between the tape and the coating. Quickly peel the tape off vertically upwards. Test results are as follows: Figure 2 As shown. Visually inspect the coating peeling in the cut area and grade it according to the GB / T9286-2021 grading standard: Grade 0: Completely smooth cut edges, no coating peeling within the grid (best); Grade 1: Minor peeling at the cut intersections, but the peeling area does not exceed 5%; Grade 2: Peeling area is 5-15%; Grade 3: Peeling area is 15-35%; Grade 4: Peeling area is 35-65%; Grade 5: Peeling area exceeds 65% (worst). Three different locations were tested for each group of test pieces, and the average value was taken.

[0055] Cross-sectional scanning electron microscopy observation: Each specimen was cut along the cross-sectional direction using wire cutting. After mounting, grinding, and polishing, the microstructure of the coating cross-section was observed using a scanning electron microscope, focusing on the density and the bonding between the coating and the substrate. The test results were referenced. Figure 3-6 As shown in Table 1, the test results above are summarized.

[0056] Table 1: Adhesion test results of the examples and comparative examples Cross-cut adhesion rating Level 0 Level 3 Level 2 Level 2 Area of ​​coating peeling off within the mesh (%) 0 Approximately 30 Approximately 15 Approximately 8 Cross-sectional scanning electron microscopy observation The coating layer and the base layer are densely and continuously coated. Large areas of the covering layer have detached from the base layer. Partial detachment of the covering layer from the base layer The density of the overlay layer is discontinuous with that of the base layer. As shown in Table 1, the adhesion of the cross-cut method in Example 1 reached level 0 (optimal). The cross-sectional SEM showed that the anchor solid in the pit was dense and without air pockets, and the cover layer and anchor solid were fused and continuous, indicating that the technical solution of the present invention can achieve excellent adhesion on both nickel foam and nickel plate substrates.

[0057] Comparative Example 1 omitted the cleaning process, and the slurry on the surface of the peaks was dried directly without removal, becoming integrated with the slurry in the pits and failing to form a selective anchoring structure. The cross-cut adhesion rating was only level 3, and cross-sectional SEM showed visible gaps between the coating and the substrate, with a large area of ​​the coating peeling off from the base layer. This indicates that the cleaning process is a crucial step for selective filling of pits. Only by removing the slurry from the surface of the peaks can the independent formation of the anchoring body in the pits be guaranteed. If this step is omitted, an effective mechanical anchoring cannot be formed between the coating and the substrate.

[0058] Comparative Example 2 completely filled the pit without applying a cover coat. There was no space left in the pit for the cover coat slurry to enter, and a continuous T-shaped interlocking structure could not be formed between the anchor and the cover coat. Cross-sectional SEM showed that part of the cover coat detached from the substrate, and the adhesion was lower than in Example 1. This demonstrates that leaving space and applying a second coat are prerequisites for the formation of the T-shaped interlocking structure. If the pit is completely filled without any space, there is a lack of physical connection between the anchor and the cover coat, and the adhesion cannot reach its optimal level.

[0059] Comparative Example 3 omitted the horizontal settling step. Air bubbles in the slurry within the pits were trapped inside the anchor body during subsequent secondary spraying and curing. Cross-sectional SEM showed discontinuous density between the coating and the substrate, and the adhesion was lower than in Example 1. This indicates that even with air pockets in the anchor body, pit filling and cleaning can still provide a certain degree of anchoring effect. However, optimal adhesion can only be achieved after horizontal settling to allow the slurry to fully settle and compact. This demonstrates a synergistic effect between the various process steps, none of which can be omitted.

[0060] In summary, this invention achieves excellent adhesion by using a complete process chain, including cleaning and removing slurry from the surface of the protrusions, controlling the filling height of the pits, horizontally placing the surface for gravity settling, and then applying a second coat to form a cover layer. This process densifies the anchoring solids within the pits and allows them to fuse with the cover layer inside the pits to form a T-shaped locking structure.

[0061] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A spraying process for improving the adhesion of a sprayed coating, characterized in that, Includes the following steps: The substrate surface is treated to form an uneven structure with pits and peaks, and the opening width of the pits is controlled to be 50-500 μm, the pit depth to be 30-100 μm, and the surface roughness to be 30-80 μm. The slurry is sprayed onto the substrate surface using a spraying device with a spraying pressure of 1.5–4.0 MPa and a spraying angle of 30–60°. The slurry impacts the substrate surface at an angle, causing it to enter the pits under the spraying pressure and accumulate at the bottom of the pits. At the same time, the angled impact causes the slurry to spread along the inner wall of the pits. The slurry covers both the convex surface of the substrate and the inside of the pits. The spraying amount is controlled so that the slurry filling height in the pits is 1 / 3 to 2 / 3 of the pit depth, leaving a reserved space at the top of the pits. Before the slurry dries, the substrate surface is cleaned, including scraping and air purging. When the substrate is a dense and rigid nickel plate, scraping is used. When the substrate is a foamed nickel or a porous and flexible metal fiber felt, air purging is used to remove the slurry covering the surface of the peaks, while ensuring that the top of the slurry remaining in the pits does not exceed the top surface of the peaks. The base is placed horizontally, allowing the slurry in the pit to settle naturally under gravity, expelling air bubbles and forming a compact anchor body. The slurry is sprayed onto the substrate surface again using a spraying device. The spraying pressure of the spraying device is 0.3 to 1.2 MPa, and the spraying angle is 70 to 90°. The slurry settles vertically or nearly vertically onto the substrate surface in a fine atomized state, forming a uniformly thick covering layer. This layer will not damage the already formed anchor body due to excessive impact. The covering layer forms a covering layer on the surface of the anchor body and the protruding surface of the substrate. The slurry in the covering layer enters the reserved space in the pit and merges with the top of the anchor body to form a continuous and integrated structure. The coating is cured to form a coating that adheres to the surface of the substrate.

2. The spraying process for improving the adhesion of the sprayed coating according to claim 1, characterized in that: The method for treating the substrate surface to form a concave-convex structure with pits and peaks is as follows: the substrate surface is treated by physical impact, chemical dissolution or thermal ablation to form randomly distributed or regularly arranged pits and peaks on the substrate surface.

3. The spraying process for improving the adhesion of the sprayed coating according to claim 1, characterized in that: The scraping process includes: scraping along the substrate surface with a scraper, with a gap of 0 to 30 μm between the scraper and the top surface of the peak. The slurry on the surface of the peak is scraped off by the scraper, while the slurry in the pit is not in contact with the scraper because it is lower than the top surface of the peak, and is thus retained inside the pit.

4. The spraying process for improving the adhesion of the sprayed coating according to claim 1, characterized in that: The airflow purging process includes: using compressed air to tangentially purge along the substrate surface at a speed of 10–30 m / s. The shearing force of the airflow is used to blow away the slurry covering the surface of the peaks, while the slurry in the pits is kept inside the pits because it is lower than the top surface of the peaks and avoids the shearing effect of the airflow.

5. The spraying process for improving the adhesion of the sprayed coating according to claim 1, characterized in that: After cleaning and before the substrate is horizontally leveled, apply a pressure pulse towards the bottom of the pit to the top of the slurry inside the pit. Set the pressure pulse to 0.1-0.5 MPa, the pulse duration to 0.1-1.0 seconds, and the number of pulses to 1-5 times, so as to force the slurry inside the pit to adhere tightly to the bottom and inner wall of the pit.

6. The spraying process for improving the adhesion of the sprayed coating according to claim 1, characterized in that: During the horizontal settling process, mechanical vibration with a frequency of 10-30Hz and an amplitude of 0.1-0.5mm is applied to accelerate the rise of residual air bubbles inside the slurry in the pit to the liquid surface for discharge.

7. The spraying process for improving the adhesion of the sprayed coating according to claim 1, characterized in that: After the coating is applied and before curing, a second cleaning process is performed along the substrate surface to remove excess slurry at the peaks of the coating surface where the thickness is greater than that at the pits, so that the difference between the coating thickness at the top of the peaks and the coating thickness above the pits does not exceed 5μm.

Citation Information

Patent Citations

  • Method for improving binding force of electrolytic copper foil and base material under low roughness and electrolytic copper foil

    CN121087577A

  • Spraying process of yttrium oxide composite coating with high corrosion resistance and wear resistance

    CN122279454A